2006
DOI: 10.1080/08958370600685798
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Exposure to Wood-Smoke Particles in Healthy Humans: Effects on Markers of Inflammation, Coagulation, and Lipid Peroxidation

Abstract: Particulate air pollution is known to increase cardiovascular morbidity and mortality. Proposed mechanisms underlying this increase include effects on inflammation, coagulation factors, and oxidative stress, which could increase the risk of coronary events and atherosclerosis. The aim of this study was to examine whether short-term exposure to wood smoke affects markers of inflammation, blood hemostasis, and lipid peroxidation in healthy humans. Thirteen subjects were exposed to wood smoke and clean air in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
125
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(136 citation statements)
references
References 50 publications
10
125
0
1
Order By: Relevance
“…Scrubbers removing sulfur dioxide from power plant emissions may increase carbon dioxide (CO 2 ) emissions due to higher energy use (Randolph and Dolsak 1996). Conversely, burning of biomass has no net CO 2 emissions if sustainably sourced, but produces local emissions of particulate matter (PM) with adverse health effects (Barregard et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Scrubbers removing sulfur dioxide from power plant emissions may increase carbon dioxide (CO 2 ) emissions due to higher energy use (Randolph and Dolsak 1996). Conversely, burning of biomass has no net CO 2 emissions if sustainably sourced, but produces local emissions of particulate matter (PM) with adverse health effects (Barregard et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Residential wood combustion has been associated with adverse health effects on a societal level in epidemiological studies as well as with more limited number of subjects in chamber exposure studies (Boman et al, 2003;Barregard, et al, 2006;Sehlstedt et al, 2010). There is, however, insufficient evidence available to decide whether particles from wood combustion are more or less toxic than other combustion-derived particles and ambient fine particles in general (Naeher et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that exposure to air pollution, including particulate matter, is associate with cardiovascular morbidity and mortality (Miller et al, 2007). Not only trafficrelated air pollution, emissions from biomass burning may also be linked with adverse cardiovascular effects (Swiston et al, 2008;Barregard et al, 2006;Tan et al, 2000). Two suggested possibilities on the explanation of particular matter associated cardiovascular diseases are 1) a systemic inflammatory response following pulmonary deposition of particles and 2) endothelial dysfunction resulting from the release of inflammatory mediators (Bai et al, 2007;Brook et al, 2004).…”
mentioning
confidence: 99%